2020
DOI: 10.3390/ijms21134593
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Hydrogen Sulfide and Other Signal Molecules Regulates Plant Growth and Development

Abstract: Hydrogen sulfide (H2S), once recognized only as a poisonous gas, is now considered the third endogenous gaseous transmitter, along with nitric oxide (NO) and carbon monoxide (CO). Multiple lines of emerging evidence suggest that H2S plays positive roles in plant growth and development when at appropriate concentrations, including seed germination, root development, photosynthesis, stomatal movement, and organ abscission under both normal and stress conditions. H2S influences these processes by altering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 122 publications
(203 reference statements)
0
32
0
Order By: Relevance
“…It has also shown strong concentration dependent affinity for reactions as it can disrupt mitochondrial cytochrome activity and even reduce mitochondrial respiration ( Mancardi et al, 2009 ). Surprisingly, research in recent years has unraveled the significance of H 2 S as a gasotransmitter that promotes plant growth and development at various stages of plant life cycle ( Xuan et al, 2020 ). Other than algae, fungi, and few prokaryotes, plants are known to take leverage of taking up the naturally occurring sulfate (SO 4 2– ) source of S from soil and incorporate it into organic forms ( Takahashi et al, 2011 ).…”
Section: Occurrence and Biosynthesis Of H 2 S In Pmentioning
confidence: 99%
“…It has also shown strong concentration dependent affinity for reactions as it can disrupt mitochondrial cytochrome activity and even reduce mitochondrial respiration ( Mancardi et al, 2009 ). Surprisingly, research in recent years has unraveled the significance of H 2 S as a gasotransmitter that promotes plant growth and development at various stages of plant life cycle ( Xuan et al, 2020 ). Other than algae, fungi, and few prokaryotes, plants are known to take leverage of taking up the naturally occurring sulfate (SO 4 2– ) source of S from soil and incorporate it into organic forms ( Takahashi et al, 2011 ).…”
Section: Occurrence and Biosynthesis Of H 2 S In Pmentioning
confidence: 99%
“…Recent studies revealed that H 2 S plays a positive role in regulating plant growth. Xuan et al considered the H 2 S roles in cellular processes and also indicated all possible crosstalk between H 2 S and phytohormones [ 12 ]. Interestingly, the authors suggested that H 2 S may affect the protein activities and subcellular localization by contributing to post-translational modification.…”
Section: Cell Signaling Related To Plant Acclimationmentioning
confidence: 99%
“…Additionally, the reduction of auxin content can increase the sensitivity of the abscission zone to ethylene [42]. Hence, once the auxin content in the abscission zone decreases, the sensitivity of the abscission zone to ethylene will increase, and even a little of ethylene will trigger shedding [43]. Therefore, auxin content in the abscission zone plays a vital role in regulating shedding.…”
Section: Phytohormones Involve In the Fruitlet Abscission Of Sweet Chmentioning
confidence: 99%